2012
DOI: 10.1021/es300988p
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Oxidation of Arsenite to Arsenate in the Presence of Goethite

Abstract: The photochemistry of an aqueous suspension of goethite in the presence of arsenite (As(III)) was investigated with X-ray absorption near edge structure (XANES) spectroscopy and solution-phase analysis. Irradiation of the arsenite/goethite under conditions where dissolved oxygen was present in solution led to the presence of arsenate (As(V)) product adsorbed on goethite and in solution. Under anoxic conditions (absence of dissolved oxygen), As(III) oxidation occurred, but the As(V) product was largely restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 44 publications
4
45
2
Order By: Relevance
“…The concentration of As(III) and goethite were chosen to ensure that the ratio of As to Fe (Fe/As z 100)after incubation was appropriate for the determination of the ratio of As(III) and As(V) by XANES analysis. In other studies on As(III) oxidation in the presence of iron oxides, the Fe/As ratio ranged from 5 to 580 (Ona-Nguema et al, 2005Bhandari et al, 2011Bhandari et al, , 2012. The flasks were shaken at 25 C at 150 rpm for 10 h. The adsorption reached equilibrium in 10 h. Abiotic control experiments of goethite only were also conducted.…”
Section: Effect Of Contact Order Of Bacteria and Goethite On The Oxidmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of As(III) and goethite were chosen to ensure that the ratio of As to Fe (Fe/As z 100)after incubation was appropriate for the determination of the ratio of As(III) and As(V) by XANES analysis. In other studies on As(III) oxidation in the presence of iron oxides, the Fe/As ratio ranged from 5 to 580 (Ona-Nguema et al, 2005Bhandari et al, 2011Bhandari et al, , 2012. The flasks were shaken at 25 C at 150 rpm for 10 h. The adsorption reached equilibrium in 10 h. Abiotic control experiments of goethite only were also conducted.…”
Section: Effect Of Contact Order Of Bacteria and Goethite On The Oxidmentioning
confidence: 99%
“…It is reported that goethite interacting with dissolved Fe(II) produced the highest redox activity compared with other Fe(III) (oxy)hydroxides (Elsner et al, 2004). Photoinduced oxidation of As(III) by goethite has also been reported and can be significantly restricted by humic acid (Bhandari et al, 2012;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In general, As(V) is stable in aerobic environment and As(III) often exists in anaerobic environment. The toxicity of arsenic species is different, generally the toxicity of inorganic arsenic compounds is about 100 times higher than organic arsenic compounds, and the toxicity of inorganic As(III) compounds are approximately 60-80 times higher to humans than As(V) compounds [13][14][15]. So the world faces major threat to community health from the water supplies with contamination, which has been a clear common view, and stimulated many studies to develop new technologies for water purification.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, microbial and photochemical processes are important in the environment because they can cause the reduction and/or oxidation of arsenic and iron Langner et al, 2000;Emett et al, 2001;Bhandari et al, 2011Bhandari et al, , 2012. Once iron oxide minerals are present, arsenic will adsorb onto these minerals and might undergo surface mediated reduction or oxidation reactions (Yan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Abiotic oxidation of As(III) by dissolved oxygen is a possible mechanism of species transformation although the process is relatively slow (Zhao et al, 2011). Recent studies have shown that photoinduced oxidation of As(III) to As(V) can occur in the presence of nanoferrihydrite and goethite (Bhandari et al, 2011(Bhandari et al, , 2012. Bhandari et al (2011) assumed that in As(III)-ferrihydrite system, the oxidation of As(III) occurred on the ferrihydrite surface until the surface becomes saturated with As(V).…”
Section: Introductionmentioning
confidence: 99%